The Human and the Non-Human in the Prose of László Krasznahorkai and Film of Béla Tarr - Bradić, Marijeta (Studia ethnologica Croatica, 2024)
László Krasznahorkai and Béla Tarr are contemporary Hungarian authors known for their long-lasting collaboration. In the late stage of his film-directing career (1988 – 2011), Tarr adapted several Krasznahorkai's novels, while the screenplay of his last film – The Turin Horse (A torinói ló, 2011) – was written by Krasznahorkai himself. The traces of Krasznahorkai's style are evident in Tarr's films not only on the level of themes and motives, but also on the level of form. Some of the main characteristics of their collaborative work include setting up an apocalyptic tone, slow flow of time, and frequent animalistic motives (e.g. cow herds grazing in the opening scene of Sátántangó, a taxidermied whale as the central motif in Werckmeister Harmonies, a horse as a character in The Turin Horse). What makes both of these authors distinctive is their interest in nonhuman subjects, namely the animals. Therefore, this article will focus on their two apocalyptic works – Krasznahorkai’s novella Animalinside (2011) and Tarr’s The Turin Horse – starting from the assumption that Krasznahorkai uses “animal narrators” in Animalinside, while Tarr aims to depict the inner life of an animal in The Turin Horse (Bernaerts et al. 2014). Their shared stylistic and formal characteristics result in similar effects for the reader/viewer and are the product of a “double dialectic”: empathy with non-human subject and estrangement, that is, a subversion of assumptions and expectations about animal subjects on one hand, and the subversion of human “experientiality” on the other (Bernaerts et al. 2014; Fludernik 1996). Starting from these assumptions, the article will consist of comparative analysis of narrative techniques in these two media, i.e., in the aforementioned novella and film, which generate similar effects and serve the same idea: challenging anthropocentric worldviews.